Soft toys cut out and sew your own original toys - Gerlings, Sara. (London Arcturus Publishing Limites, 2012)
This is a step by step guide to the rewarding craft of soft toy making. It features 13 original toys with pattern pieces and instuerctions for making them up by hand or machine.
Keywords: Soft toy making -- Juvenile literature; Soft toys -- Juvenile literature; Textile crafts -- Juvenile literature